DIAGNOSTIC METHODS FOR EARLY DETECTION OF PARTIAL PRIMARY TOOTH AGENESIS IN CHILDREN (0–18 YEARS) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Partial primary tooth agenesis is a congenital developmental anomaly characterized by the absence of one or more teeth due to disturbances in odontogenesis. Early diagnosis plays a crucial role in preventing secondary occlusal disorders, craniofacial asymmetry, and psychosocial complications. The aim of this study was to evaluate modern diagnostic methods used for early detection of partial tooth agenesis in children across different age groups (0–18 years) and to assess their clinical effectiveness. A retrospective and prospective clinical analysis was conducted involving 980 pediatric patients who underwent clinical examination and radiographic evaluation. Diagnostic tools including visual clinical assessment, panoramic radiography, cone-beam computed tomography (CBCT), and genetic evaluation were analyzed. The results demonstrate that panoramic radiography remains the primary screening method during mixed dentition, while CBCT provides superior three-dimensional visualization in complex cases. Early diagnosis before the age of 10 significantly improves orthodontic planning and treatment outcomes. The study confirms that age-specific diagnostic algorithms increase detection accuracy and optimize long-term functional rehabilitation.